No time like the present - Gordimer, Nadine (New York : Farrar, Straus and Giroux, 2012)
At the heart of the story is an interracial couple, Steve and Jabulile, living in a newly, tentatively free South Africa, he a university lecturer she a lawyer, both comrades in the struggle for freedom against apartheid. Once clandestine lovers under a racist law forbidding sexual relations between black and white, they are now parents of children born in freedom. They have a daughter, Sindiswa; they move to the suburbs; there is another child, a boy this time. There is nothing so extraordinary about their lives, and yet, in telling their story, and the stories of their friends and families, the author manages to capture the tortured, fragmented essence of a nation struggling to define itself in the post-apartheid world of Thabo Mbeki and Jacob Zuma.
Keywords: Interracial marriage -- South Africa; Families -- South Africa; Apartheid -- South Africa; Interpersonal relations; South Africa -- Social conditions -- 1994-